Transa (1972): a canção de exílio de Caetano Veloso - Colombari, Rodolfo José (Universidade Federal de São Carlos, 2025)
This study aims to analyze Caetano Veloso's album Transa (1972), composed and produced at the time of his exile in London due to the military dictatorship established in Brazil since 1964, aggravated after the AI-5, in order to perceive it as a song from exile. Based on Bernd's study (1992), we understand Transa as a desacralizing work in the construction of a national identity, since it is composed of an anthropophagic mixture (Andrade, 1928) of elements that refer to the popular, the historically excluded classes and Afro-Brazilian ancestral culture, while incorporating Gregório de Matos, Dorival Caymmi and João Gilberto with elements of mass culture such as the Beatles' rock'n roll and the English language. Orality, the means by which popular culture has been transmitted through time, finds a way to materialize on the record and in the composition of songs, forming a double body of the medium (Debray, 2000) made up of the institutional dimension (materialized organization) and its material dimension (organized matter), in other words, the object responsible for the transmission and crystallization of certain ideas that refer to the popular and oral culture of the excluded classes, such as blacks, mestizos and indigenous people, and which are mobilized and organized by Caetano Veloso in order to sing about his country as an exile.
Transa (1972): Caetano Veloso's song of exile
Keywords: LP Transa; Caetano Veloso; Mediologia; Identidade Nacional; Mediology; National identity; LINGUISTICA, LETRAS E ARTES::LETRAS; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURA BRASILEIRA; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::SOCIOLINGUISTICA E DIALETOLOGIA